The Forest Behind the Tree: Heterogeneity in How US Governor's Party Affects Black Workers - Guy Tchuente; Johnson Kakeu; John Nana Francois (Global Labor Organization (GLO), 2021)
Income inequality is a distributional phenomenon. This paper examines the impact of U.S governor's party allegiance (Republican vs Democrat) on ethnic wage gap. A descriptive analysis of the distribution of yearly earnings of Whites and Blacks reveals a divergence in their respective shapes over time suggesting that aggregate analysis may mask important heterogeneous effects. This motivates a granular estimation of the comparative causal effect of governors' party affiliation on labor market outcomes. We use a regression discontinuity design (RDD) based on marginal electoral victories and samples of quantiles groups by wage and hours worked. Overall, the distributional causal estimations show that the vast majority of subgroups of black workers earnings are not affected by democrat governors' policies, suggesting the possible existence of structural factors in the labor markets that contribute to create and keep a wage trap and/or hour worked trap for most of the subgroups of black workers. Democrat governors increase the number of hours worked of black workers at the highest quartiles of earnings. A bivariate quantiles groups analysis shows that democrats decrease the total hours worked for black workers who have the largest number of hours worked and earn the least. Black workers earning more and working fewer hours than half of the sample see their number of hours worked increase under a democrat governor.
Keywords: D72; J15; J22; J31; R23; 330; U.S. State Policy; Black Workers; US Labor Market; RDD; Governors' Effects Heterogeneity; Bivariate Quantile Causality